PENERAPAN WORDWALL PADA MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Firman Sanjaya; Leni Maryani; Hasybi Maulana (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This study aims to determine the improvement of students' critical thinking skills in experimental and control classes. The research approach used is a quantitative approach with experimental methods. This research design is nonequivalent control group design. This research was conducted at SMA Sumatra 40 Bandung involving 2 classes, namely class X IPS 1 as an experimental class with the application of wordwall in problem-based learning model and class X IPS 2 as a control class with the application of direct learning model. The instruments used were pretest and posttest sheets and observation sheets for the implementation of the model in the experimental class. The results showed that there was an increase in students' critical thinking skills in the experimental class, namely the pretest score of 49.03 and the posttest score of 78.77, an increase of 29.74. While in the control class the pretest score was 46.53 and the posttest score was 60.47, an increase of 13.93. Meanwhile, the implementation of the problem-based learning model in the experimental class has been carried out in accordance with the learning design listed on the lesson plan (RPP). This research produces results that can provide benefits to stakeholders, namely teachers can utilize learning models and wordwall media in the classroom to improve the quality of student learning. For school principals, they can provide policies and directions regarding learning schemes that can be carried out in the classroom by teachers. Students can participate more actively in developing critical thinking skills. For further researchers, they can update the research that has been studied.